(untitled) (Research, Society and Development, 2022)
Considering the importance of palliative therapy to the integrality of care and guaranteeing the quality of life (QoL) of cancer patients, the present study aims to carry out a bibliographic survey to, thus, ascertain the QOL of cancer patients in Palliative Care (PC) ). The present study is a narrative review of the literature. The selected database was the Google Scholar virtual library. The inclusion criteria adopted in the selection were: studies dated in the last 10 years, in Portuguese and English with the full text available in full for reading and that were within the focus of this study. Publications that were not in line with the theme or that did not describe the role of nurses in PCs were excluded. Initially, 1,130 publications were found and, after applying the inclusion and exclusion criteria, 42 remained. After reading the titles and abstracts, 20 articles were retrieved to be read in full. After reading, 10 articles were selected to compose this review. The analysis of the 10 studies that composed this review revealed concerns of health professionals, still quite highlighted, who seek general and specific measurement tools to identify predictors that can positively or negatively affect the health-related quality of life (HRQoL) for patients with advanced cancer with no possibility of curative treatment. Therefore, palliative care needs to be strengthened. These studies provide evidence of signs and symptoms that affect the HRQoL of these patients to varying degrees.